GAMBARAN PERCEIVED STIGMA PADA PENDERITA TBC - Rima Eka Setiawati; Wasisto Utomo; Yulia Rizka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Perceived stigma is a person's perception and evaluation of the imprint or label society assigns to people deemed abnormal, abnormal, alien, or different from the average person. Stigma that is perceived to be unfavorable to a person can lead to an individual's perception of experiencing social stigma. This study aimed to determine the description of stigma among tuberculosis patients in Rejosari and Payung Sekaki health centers in 2021. This study used a descriptive method. The sample in this study consisted of 56 individuals using a total sampling technique. The results of univariate test showed that most TB patients were older than 35 years (67.9%), their gender was mainly male (66.1%), and the highest education level was junior high school (48.3%). Patients were not working (64.3%). %), the perceived stigma was good (55.4%). Based on the results obtained, it shows that the stigma of TB patients has a good stigma of their disease.Keywords: Perceived, Stigma, Tuberculosis